The freelance editor's handbook : a complete guide to making your business thrive - Bills, Suzy, 1981- (University of California Press, 2021)
"This book provides information that's relevant not only to editors who are new to freelancing but also to editors who've been freelancing for a while (even for decades) and want to refine their processes to make their businesses more enjoyable, efficient, and financially rewarding, whether freelance editing is a part-time or full-time career. The book covers topics such choosing a business entity, establishing a business mindset, marketing to ideal clients, creating a website, determining how to price services, developing a contract, maximizing productivity, achieving work/life balance, paying taxes, managing cash flow, choosing which types of insurance to buy, and saving for retirement"--